Muhammad Nur Alif Re'dzuan sacrifices for beloved father - UMP, PNC (2019)
Muhammad Nur Alif Re'dzuan, 24, quitted his job as a programmer and graphic designer in a company based in Cyberjaya to look after his father, Re'dzuan Yusof, 59, who underwent a brain surgery due to aneurysm last April.